PENGARUH FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - RIZKA AMALIA; DEA ANNISA (Pusat P2M Politeknik Negeri Batam, 2023)
This study aims to examine and obtain empirical evidence regarding the Effect of Pentagon Fraud on Financial Statement Fraud with the Audit Committee as a Moderating Variable in manufacturing companies in the Basic Industry and Chemical sectors listed on the Indonesia Stock Exchange in 2018–2021. The research sample collection technique used a purposive sampling method, resulting in a sample of 21 companies with a total of 84 observations and using an associative quantitative approach. The data analysis technique used was multiple linear regression analysis, with data processing using Eviews 12. The results showed that the Ineffective Oversight as a Pentagon Fraud mechanism had an effect on Financial Statement Fraud. Financial Stability, Auditor Change, Board of Directors Change, Frequency of Appearance of CEO Images as a Pentagon Fraud mechanism has no effect on Financial Statement fraud. The Audit Committee cannot moderate Financial Stability, Oversight Ineffectiveness, Auditor Change, Directors Change, CEO Image Appearance as a Pentagon Fraud mechanism against Financial Statement Fraud.